Geometry Optimization of Power Production Turbine for a Low Enthalpy (≤100˚C) ORC System. (August 2015) - Efstathiadis, T.; Kalfas, A.I.; Seferlis, P.; Kyprianidis, K.G.; Rivarolo, M.
Abstract: The present paper is examining the geometry optimization of a power production turbine, in the range of 100 kWel, for a low enthalpy Organic Rankine cycle system (≤100˚C). In the last years, accelerated consumption of fossil fuels has caused many serious environmental problems such as global warming, ozone layer destruction and atmospheric pollution. It is this reason that a growing trend towards exploiting low-enthalpy content energy sources has commenced and led to a renewed interest in small-scale turbines for Organic Rankine Cycle applications. The design concept for such turbines can be quite different from either standard gas or steam turbine designs. The limited enthalpic content of many energy sources imposes the use of organic working media, with unusual properties for the turbine. A versatile cycle design and optimization requires the parameterization of the main turbine design. There are many potential applications of this power-generating turbine, including geothermal and concentrate solar thermal fields or waste heat of steam turbine exhausts. An integrated model of equations has been developed, thus creating a model to assess the performance of an organic cycle for various working fluids such as R134a and isobutane-isopentane mixture. The most appropriate working fluid has been chosen, taking its influence on both cycle efficiency and the specific volume ratio into consideration. This choice is of particular importance at turbine extreme operating conditions, which are strongly related to the turbine size. In order to assess the influence of various design parameters, a turbine design tool has been developed and applied to define the geometry of blades in a preliminary stage. Finally, as far as the working fluid is concerned, the mixture of 85% isopentane-15% isobutane has been chosen as the most suitable fluid for the low enthalpy ORC system, since its output net power is 10% higher compared to the output net power of R134a.